Tuning for the rate and duration of frequency modulated sweeps in the inferior colliculus of the big brown bat - Morrison, James (My University, 2015)
I investigated how the auditory system encodes frequency modulated (FM) sweeps, by recording neuronal responses in the auditory midbrain (inferior colliculus, IC) of the big brown bat, (Eptesicus fuscus) while searching for the responses of so-called “FM duration-tuned neurons (DTNs)”. The responses of DTNs are selective for stimulus duration. My project investigated how the responses of FM DTNs encode the two temporal properties of FM sweeps: sweep duration, and the rate of frequency change (i.e. sweep rate). Based on previous studies, it was unclear whether FM DTNs were tuned to signal duration like classic DTNs, or simply the rate of FM. I addressed this question using single unit extracellular recordings from DTNs in the IC of E. fuscus. First, I measured the spectral tuning parameters of a cell, and then FM pulses were randomly varied in duration to measure the temporal bandwidth of duration tuning of the cell. To separate FM rate tuning from duration tuning, the duration tuning of the cells was tested at different sweep bandwidths (i.e. doubled or halved) while keeping the center frequency constant. If a neuron is tuned to stimulus duration, then the range of excitatory signal duration(s) should not change with changes in FM bandwidth; however, if the cell is tuned to the rate of FM, then the range of excitatory durations should corresponed to the same FM rate of each altered bandwidth. A Bayesian model comparison showed that an overwhelming majority of FM DTNs were in fact tuned to sweep rate. Thus, I conclude that the dominant response parameter for temporal tuning of FM cells in the IC of the bat is not signal duration, but FM sweep rate.